Determination of elemental impurities in acyclovir ointment and raw materials using microwave acid digestion (MW-AD) and ICP-MS - Gonzalez, Mario H. [UNESP]; Da Silva, Caroline S.; Amaral, Clarice D. B.; Bianchi, Silmara R.; De Oliveira, Luciano H. B. [UNESP]; Coelho, Jéssica S. [UNESP]; Oliveira, Andrea; Nogueira, Ana Rita A. (Sociedade Brasileira de Quimica (SBQ), 2017)
Inorganic elements present in pharmaceutical products were determined by inductively coupled plasma-mass spectrometer (ICP-MS), employing microwave acid digestion as a sample preparation method. The most abundant isotopes, 75As+, 65Cu+, 52Cr+, 58Ni+, 208Pb+, and 51V+, were determined in acyclovir ointment and its constituents. Elemental impurities in the pharmaceutical samples were determined using an inductively coupled plasma-universal cell technology-mass spectrometer (ICP-UCT-MS) operated in kinetic energy discrimination (KED) and standard mode. The accuracy of the method was assessed by means of addition and recovery experiments. Except for Cr, spiked recoveries of the elements added to the samples before microwave acid digestion (MW-AD) step were between 95.1 and 126%, and after MW-AD step ranged from 85.6 to 132%. Limits of detection (LOD) obtained by proposed method is in agreement to those required by the U.S. Pharmacopeia Convention (USP), showing that the ICP-MS technique is well suited for quantification of these elements. The LOD's (ng L-1) for 51V+, 52Cr+, 58Ni+, 65Cu+, 75As+ and 208Pb+ in 1% v v-1 HNO3 medium were: 2.2, 81.3, 91.9, 6.9, 0.2 and 3.1, respectively. The concentration of the analytes in these samples presented a wide range, varying from 2.3 ± 0.8 μg kg-1 for As to 3446 ± 47 μg kg-1 for Cr.
Keywords: Acyclovir; Elemental impurity; ICP-MS; Microwave acid digestion (MW-AD); Pharmaceutical product